STRATEGI PENGEMBANGAN PRODUKSI DAN SALURAN PEMASARAN PUPUK ORGANIK DI KECAMATAN KALIDONI KOTA PALEMBANG (STUDI KASUS SATKER INSTALASI 3R) - Ardianto, Rio; Iskandar, Sutarmo (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2021)
This research was carried out to determine the strategy for developing production and marketing chanels for organic fertilizer (case study of the 3r instalation work unit from november 2020 to january 2021. The research method used was a survey. The sampling method used in this research is to determine the expert respondent consisting of a total of 8 people (purposive sampling), where the data obtained is qualitative data from expert respondent interviews which are then analyzed using the SWOT analysis method. The data collection method used in this study in primary data obtained from direct observations and interviews with respondent, secondary data obtained from various library sources, related agencies or institutions as well as institutions and interviews with respondents, secondary data obtained from various library sources, related agencies or institutions as well as institutions related to this research. The data processing method used is descriptive qualitative. By using SWOT analysis. The result show that the alternative strategy for developing production and marketing channels for organic fertilizer production by the 3r installation unit is the SO (strength-opportunities) strategy, which is to increas the amount of production and maintain the quality of fertilizer product so that the demand for consumers are met and increas sales creating variations of fertilizer, and also optimizing packaging by creating newer fertilizer brands, production ages, so that fertilizer sales can enter modern markets to expand business development. Creating organic fertilizer business credit by making good and attractive product quality so that consumers are interested.